"I Want to Know More!": Children Are Sensitive to Explanation Quality When Exploring New Information. Issue 1 (4th January 2019) - Mills, Candice M.; Sands, Kaitlin R.; Rowles, Sydney P.; Campbell, Ian L.
Abstract: When someone encounters an explanation perceived as weak, this may lead to a feeling of deprivation or tension that can be resolved by engaging in additional learning. This study examined to what extent children respond to weak explanations by seeking additional learning opportunities. Seven‐ to ten‐year‐olds ( N = 81) explored questions and explanations (circular or mechanistic) about 12 animals using a novel Android tablet application. After rating the quality of an initial explanation, children could request and receive additional information or return to the main menu to choose a new animal to explore. Consistent with past research, there were both developmental and IQ‐related differences in how children evaluated explanation quality. But across development, children were more likely to request additional information in response to circular explanations than mechanistic explanations. Importantly, children were also more likely to request additional information in direct response to explanations that they themselves had assigned low ratings, regardless of explanation type. In addition, there was significant variability in both children's explanation evaluation and their exploration, suggesting important directions for future research. The findings support the deprivation theory of curiosity and offer implications for education.